Melissa - Gino, Alex (Scholastic Press, 2022)
Though most of her peers see George as a boy, she thinks she is really a girl on the inside. When the class presents the play Charlotte's Web, George isn't allowed to try out for the role of Charlotte. George's best friend, Kelly, comes up with a plan for George to be Charlotte and show everyone who she really is.